Negative-electrode-free sodium ion solid-state battery and preparation method thereof
By designing a negative electrode-free structure in a sodium ion battery and using the conductive agent layer to increase the negative electrode stiffness and conductive network, the problem of insufficient energy density and safety performance of sodium ion battery is solved, and higher energy density and cycling performance are achieved, which is suitable for industrial applications. .
Patent Information
- Application Number
- CN202411342886.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
Smart Images

Figure CN119208747A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a negative electrode-free sodium ion solid-state battery and a preparation method thereof. Background Art
[0002] Sodium-ion batteries have wide resources, low costs and small fluctuations, low electrolyte concentration, similar working principles to lithium-ion batteries, and excellent cycle performance and low-temperature performance. In the future, their application in low-speed electric vehicles, large-scale energy storage systems, mining and other high-risk industries will become increasingly important. However, the current energy density of liquid sodium-ion batteries can only reach a maximum of 160Wh / kg, which is low in energy density, large in size, and has safety performance that needs to be improved, which limits its application scenarios and has an adverse impact on the speed of the commercialization process of sodium-ion batteries.
[0003] All-solid-state batteries are regarded as one of the final forms of commercial batteries. By replacing flammable liquid electrolytes with solid electrolytes, higher energy density and better long-term cycle performance can be maintained, while providing users with safer power batteries. The energy and power density of all-solid-state batteries are largely determined by the positive electrode. In order to improve the energy density of sodium-ion batteries, a relatively common method is to use high-capacity positive electrode active materials and negative electrode active materials. However, high-capacity positive electrode active materials will lead to increased side reactions on the surface of the positive electrode, thereby reducing the cycle life of the battery, and will also bring other problems, such as electrolyte decomposition caused by increased voltage. In addition, high-capacity negative electrode materials and solid electrolytes can also be used to meet the needs. However, the alloy-type high-capacity materials such as Sn and P used in the current negative electrode materials have problems such as poor conductivity, large expansion, and more irreversible capacity loss. Therefore, to date, the realization of high energy and power density in all-solid-state batteries is still subject to many obstacles. Summary of the invention
[0004] The purpose of the present invention is to provide a sodium ion solid-state battery without a negative electrode in order to solve the above-mentioned technical problems. The battery does not use negative electrode active materials and has a higher capacity density, less irreversible capacity and higher safety performance at a lower cost.
[0005] The negative electrode-free sodium ion solid-state battery in the technical solution of the present invention is composed of n sodium ion solid-state battery units, wherein n is greater than or equal to 2, and the sodium ion solid-state battery unit includes a current collector layer, a conductive agent layer, a solid electrolyte layer and a positive electrode active material layer from bottom to top.
[0006] The present invention uses a current collector layer, a conductive agent layer, a solid electrolyte layer and a positive electrode active material layer as components to obtain a negative electrode-free sodium ion solid-state battery, which can maximize the energy density of the sodium ion battery.
[0007] Furthermore, the weight proportions of the current collector layer, the conductive agent layer, the solid electrolyte layer and the positive electrode active material layer are 0.5 to 10 parts, 0.01 to 0.10 parts, 0.1 to 10 parts and 10 to 1000 parts respectively.
[0008] Furthermore, the weight percentages of the current collector layer, the conductive agent layer, the solid electrolyte layer and the positive electrode active material layer are 2.0 to 4.0 parts, 0.01 to 0.08 parts, 0.2 to 0.6 parts and 200 to 400 parts respectively.
[0009] Furthermore, the current collector is one or more of aluminum powder, copper powder, titanium powder, nickel powder, aluminum foil, copper foil, titanium foil, nickel foil, and stainless steel foil.
[0010] Furthermore, the current collector is one or more of aluminum powder, copper powder, titanium powder, and nickel powder.
[0011] Furthermore, the conductive agent is one or more of graphene, carbon nanotubes, carbon fiber, and Ketjen black.
[0012] Furthermore, the solid electrolyte is one or more of oxides, sulfides, halides, and borohydrides.
[0013] Furthermore, the positive electrode active material is one or more of transition metal oxides, polyanion compounds, and Prussian blue / white compounds.
[0014] Furthermore, the preparation method of the sodium ion solid-state battery cell includes the following steps: first pressing the solid electrolyte powder into layers, then placing the positive electrode active material powder on one side of the solid electrolyte layer, and placing the conductive agent powder on the other side of the solid electrolyte layer. After pressing and molding, the negative electrode current collector powder is placed on the other side of the conductive agent layer, and pressed and molded again.
[0015] The present invention presses the conductive agent powder into a conductive agent layer as an intermediate layer between the current collector layer and the solid electrolyte layer, which can increase the rigidity of the negative electrode and ensure that the sodium ions are deposited evenly and smoothly, while providing a good conductive network, reducing the "dead sodium" area, and improving the cycle performance of the sodium ion battery.
[0016] Preferably, the solid electrolyte powder is pressed into a sheet having a size of 80 to 120 mm×60 to 100 mm.
[0017] Furthermore, the pressing pressure is 300-900 MPa, and the time is 5-10 min.
[0018] The present invention also provides a method for preparing the above-mentioned negative electrode-free sodium ion solid-state battery, which is to stack the sodium ion solid-state battery cells with the positive electrode active material layer facing the positive electrode active material layer, place current collector aluminum powder on the outermost positive electrode active material layer, and then press and form.
[0019] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0020] (1) The present invention uses a current collector layer, a conductive agent layer, a solid electrolyte layer and a positive electrode active material layer as components, first prepares a sodium ion solid-state battery unit, and then stacks it to obtain a sodium ion solid-state battery, which can maximize the energy density of the sodium ion battery;
[0021] (2) The conductive agent powder is pressed into a conductive agent layer, which serves as an intermediate layer between the current collector layer and the solid electrolyte layer, thereby increasing the rigidity of the negative electrode and ensuring that the sodium ions are deposited evenly and flatly;
[0022] (3) The conductive agent powder is pressed into a conductive agent layer, which can provide a better conductive network for the sodium ion solid-state battery, reduce the "dead sodium" area, and thus improve the cycle performance of the sodium ion battery;
[0023] (4) The method of the present invention for improving the energy density and safety performance of sodium ion batteries is simple, efficient, and suitable for large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of a negative electrode-free sodium ion solid-state battery cell in Example 1;
[0025] In the figure: 1-aluminum layer, 2-conductive agent layer, 3-solid electrolyte layer, 4-positive electrode active material layer. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosed content of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0027] Example 1
[0028] The method for preparing the negative electrode-free sodium ion solid-state battery of this embodiment comprises the following steps:
[0029] (1) 0.5 g Na4B 10 H 10 B 12 H 12 The powder was pressed into a 100 mm × 80 mm solid electrolyte layer at a pressure of 500 MPa for 5 min;
[0030] (2) placing a solid electrolyte layer on top of 300 g of NaNiFeMnO2 powder, a positive electrode active material, and then placing 0.05 g of graphene powder on top of the solid electrolyte layer, and pressing to form a mold at a pressure of 500 MPa for 5 min;
[0031] (3) Place 3 g of aluminum powder on one side of the conductive agent and press to form the Figure 1 The negative electrode-free sodium ion solid-state battery cell shown has a pressure of 500 MPa and a pressing time of 5 min. The obtained negative electrode-free sodium ion solid-state battery cell is stacked in 10 layers with the positive electrode active material layer facing the positive electrode active material layer, 3 g of current collector aluminum powder is placed on the surface of the positive electrode active material layer, and pressed into a sodium ion solid-state battery.
[0032] Example 2
[0033] The method for preparing the negative electrode-free sodium ion solid-state battery of this embodiment comprises the following steps:
[0034] (1) Put 0.5g Na 3.3 Zr 1.7 Lu 0.3 Si2PO 12 The powder was pressed into a 100 mm × 80 mm solid electrolyte layer at a pressure of 500 MPa for 5 min;
[0035] (2) placing a solid electrolyte layer on top of 350 g of Na2FeP2O7 powder, a positive electrode active material, and then placing 0.05 g of carbon nanotube powder on top of the solid electrolyte layer, and pressing to form the mixture at a pressure of 500 MPa for 6 min;
[0036] (3) 3 g of copper powder was placed on one side of the conductive agent and pressed to obtain a negative electrode-free sodium ion solid-state battery cell at a pressure of 500 MPa for 5 min; 8 layers of the obtained negative electrode-free sodium ion solid-state battery cell were stacked with the positive electrode active material layer facing the positive electrode active material layer, 3 g of current collector aluminum powder was placed on the surface of the positive electrode active material layer, and pressed to obtain a sodium ion solid-state battery.
[0037] Example 3
[0038] The method for preparing the negative electrode-free sodium ion solid-state battery of this embodiment comprises the following steps:
[0039] (1) 0.4 g of NaTaCl6 powder was pressed into a 100 mm × 80 mm solid electrolyte layer at a pressure of 500 MPa for 5 min;
[0040] (2) placing a solid electrolyte layer on top of 300 g of Na2CoFe(CN)6 powder, a positive electrode active material, and then placing 0.06 g of carbon fiber powder on top of the solid electrolyte layer, and pressing to form a mold at a pressure of 500 MPa for 5 min;
[0041] (3) 3 g of titanium powder was placed on one side of the conductive agent and pressed to obtain a negative electrode-free sodium ion solid-state battery unit at a pressure of 500 MPa for 5 min; 5 layers of the obtained negative electrode-free sodium ion solid-state battery unit were stacked with the positive electrode active material layer facing the positive electrode active material layer, 3 g of current collector aluminum powder was placed on the surface of the positive electrode active material layer, and pressed to obtain a sodium ion solid-state battery.
[0042] Example 4
[0043] The difference between this embodiment and embodiment 1 is that in step (1), 0.6 g Na4B 10 H 10 B 12 H 12 The powder was pressed into a solid electrolyte layer of 100 mm × 80 mm at a pressure of 500 MPa for 5 min.
[0044] Example 5
[0045] The difference between this embodiment and embodiment 1 is that in step (1), 0.7 g Na4B 10 H 10 B 12 H 12 The powder was pressed into a solid electrolyte layer of 100 mm × 80 mm at a pressure of 500 MPa for 5 min.
[0046] Example 6
[0047] The only difference between this embodiment and embodiment 1 is that in step (2), a solid electrolyte layer is placed on top of 400 g of the positive electrode active material NaNiFeMnO2 powder, and then 0.05 g of graphene powder is placed on top of the solid electrolyte layer, and pressed into shape at a pressure of 500 MPa for 5 min.
[0048] Example 7
[0049] The only difference between this embodiment and embodiment 1 is that in step (2), a solid electrolyte layer is placed on top of 500 g of the positive electrode active material NaNiFeMnO2 powder, and then 0.05 g of graphene powder is placed on top of the solid electrolyte layer, and pressed into shape at a pressure of 500 MPa for 5 min.
[0050] Example 8
[0051] The only difference between this embodiment and embodiment 1 is that in step (2), a solid electrolyte layer is placed on top of 300 g of the positive electrode active material NaNiFeMnO2 powder, and then 0.05 g of pre-pressed graphene sheets are placed on top of the solid electrolyte layer, and pressed into shape at a pressure of 500 MPa for 5 min.
[0052] Example 9
[0053] The difference between this embodiment and embodiment 1 is that in step (3), 3 g of aluminum foil with a thickness of 8 μm is placed on one side of the conductive agent, and pressed to obtain a negative electrode-free sodium ion solid-state battery, the pressure is 500 MPa, and the pressing time is 5 min.
[0054] Comparative Example 1
[0055] The preparation method of the sodium ion solid-state battery of this comparative example comprises the following steps:
[0056] (1) 0.5 g Na4B 10 H 10 B 12 H 12 The powder was pressed into a 100 mm × 80 mm solid electrolyte layer at a pressure of 500 MPa for 5 min;
[0057] (2) placing the solid electrolyte layer on top of 300 g of the positive electrode active material NaNiFeMnO2 powder and pressing it into shape at a pressure of 500 MPa for 5 min;
[0058] (3) 3 g of aluminum powder was placed on one side of the conductive agent and pressed to obtain a sodium ion solid-state battery cell at a pressure of 500 MPa for 5 min; 10 layers of the obtained negative electrode-free sodium ion solid-state battery cell were stacked with the positive electrode active material layer facing the positive electrode active material layer, 3 g of current collector aluminum powder was placed on the surface of the positive electrode active material layer, and pressed to obtain a sodium ion solid-state battery.
[0059] Comparative Example 2
[0060] The preparation method of the sodium ion solid-state battery of this comparative example comprises the following steps:
[0061] (1) 0.5 g Na4B 10 H 10 B 12 H 12 The powder was pressed into a 100 mm × 80 mm solid electrolyte layer at a pressure of 500 MPa for 5 min;
[0062] (2) placing a solid electrolyte layer on top of 300 g of NaNiFeMnO2 powder, a positive electrode active material, and then placing 0.05 g of graphite powder on top of the solid electrolyte layer, and pressing to form a mold at a pressure of 500 MPa for 5 min;
[0063] (3) 3 g of aluminum powder is placed on the solid electrolyte layer and pressed to obtain a negative electrode-free sodium ion solid-state battery unit at a pressure of 500 MPa for 5 min; 10 layers of the obtained negative electrode-free sodium ion solid-state battery unit are stacked with the positive electrode active material layer facing the positive electrode active material layer, 3 g of current collector aluminum powder is placed on the surface of the positive electrode active material layer, and pressed to obtain a sodium ion solid-state battery.
[0064] The sodium ion solid-state batteries obtained in Example 2 and Example 3 are within the voltage range of 16-28V and 10-20V, respectively. The sodium ion solid-state batteries obtained in the other examples and comparative examples are within the voltage range of 20-40V. They are first formed with a current of 0.05C, then divided with a current of 0.1C, and then the cycle retention rate of the battery is tested with a current of 0.5C. The test results are shown in Table 1.
[0065] Table 1 Electrochemical performance of sodium ion solid-state batteries
[0066]
[0067] In Examples 1-7, a current collector layer, a conductive agent layer, a solid electrolyte layer and a positive electrode active material layer are used as components to obtain a sodium ion solid-state battery with good electrochemical properties; in Example 8, a lamellar conductive agent layer is directly used, and the interaction force between the conductive agent layer and the solid electrolyte layer is significantly reduced, and the cycle performance of the obtained solid-state battery is significantly deteriorated; in Example 9, a lamellar current collector is directly used, and the bonding force between the conductive agent layer and the current collector layer is weakened, and the cycle performance of the obtained sodium ion solid-state battery is deteriorated; in Comparative Example 1, a conductive agent layer is not provided, and the conductive performance is reduced, the interaction force between the solid electrolyte layer and the current collector layer is weak, and the cycle performance is reduced; in Comparative Example 2, a conductive agent layer is formed by pressing graphite powder, and it is difficult for sodium ions to deposit into the graphite, resulting in uneven sodium ion deposition and a decrease in cycle performance.
[0068] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A negative electrode-free sodium ion solid-state battery, characterized in that: The negative electrode-free sodium ion solid-state battery is composed of n sodium ion solid-state battery units, wherein n is greater than or equal to 2, and the sodium ion solid-state battery unit includes a current collector layer, a conductive agent layer, a solid electrolyte layer and a positive electrode active material layer from bottom to top.
2. The negative electrode-free sodium ion solid-state battery according to claim 1, characterized in that: The weight proportions of the current collector layer, the conductive agent layer, the solid electrolyte layer and the positive electrode active material layer are 0.5 to 10 parts, 0.01 to 0.10 parts, 0.1 to 10 parts and 10 to 1000 parts respectively.
3. The negative electrode-free sodium ion solid-state battery according to claim 2, characterized in that: The weight parts of the current collector layer, the conductive agent layer, the solid electrolyte layer and the positive electrode active material layer are 2.0 to 4.0 parts, 0.01 to 0.08 parts, 0.2 to 0.6 parts and 200 to 400 parts respectively.
4. The negative electrode-free sodium ion solid-state battery according to claim 1, characterized in that: The current collector is one or more of aluminum powder, copper powder, titanium powder, nickel powder, aluminum foil, copper foil, titanium foil, nickel foil, and stainless steel foil.
5. The negative electrode-free sodium ion solid-state battery according to claim 4, characterized in that: The current collector is one or more of aluminum powder, copper powder, titanium powder and nickel powder.
6. The negative electrode-free sodium ion solid-state battery according to claim 1, characterized in that: The conductive agent is one or more of graphene, carbon nanotubes, carbon fibers, and Ketjen black.
7. The negative electrode-free sodium ion solid-state battery according to claim 1, characterized in that: The solid electrolyte is one or more of oxides, sulfides, halides, and borohydrides.
8. The negative electrode-free sodium ion solid-state battery according to claim 1, characterized in that: The positive electrode active material is one or more of transition metal oxides, polyanion compounds and Prussian blue compounds.
9. The negative electrode-free sodium ion solid-state battery according to claim 1, characterized in that: The preparation method of a sodium ion solid-state battery cell includes the following steps: first pressing solid electrolyte powder into layers, then placing positive electrode active material powder on one side of the solid electrolyte layer, and placing conductive agent powder on the other side of the solid electrolyte layer. After pressing and molding, negative electrode current collector powder is placed on the other side of the conductive agent layer, and pressed and molded again.
10. A method for preparing a negative electrode-free sodium ion solid-state battery as claimed in claim 1, characterized in that: The preparation method comprises stacking the sodium ion solid-state battery cells with the positive electrode active material layer facing the positive electrode active material layer, placing current collector aluminum powder on the outermost positive electrode active material layer, and then pressing and molding.
Citation Information
Cited By
Battery monomer, battery device, power utilization device and preparation process
CN121642200A
